Barriers to Surgical Innovation Research: A Canadian Study on Public Funding Trends. (October 2022) - Wang, Rachel; Kaarid, Kaija P; Sanaee, May
Background: A decline in research funding has been cited as a potential cause for limited surgical innovation in the United States. We aim to understand if this is a North American phenomenon and explore whether a lack of public funding is a barrier to surgical innovation in Canada. Methods: Publicly available funding data from Canadian Institutes of Health Research (CIHR) were reviewed from 2008 to 2019 to determine the yearly funding distributed to surgical departments. Surgical innovation studies were identified and total yearly funding was calculated. All amounts were adjusted for inflation to reflect 2019 Canadian dollar value. Results: From 2008 to 2019, surgical departments were granted 1.82–4.70% of total CIHR funding. In total, 902 grants were allocated to surgical departments and 126 (14.0%) met criteria for surgical innovation. Surgical innovation research was allocated a total annual amount ranging from 1.52 to 9.01 million CAD. There appears to be an upward trend in public funding for surgical innovation over this time period. Discussion: Contrary to the landscape in the United States, there is no evidence of decreasing trends in public funding for surgical innovation in Canada. Considerations should be given to other potential barriers precluding surgeons from participating in innovation. Conclusion: Only a small percentage of research dollars to departments in Canada are spent on innovation research, despite an overall increasing trend in total public research funding over the past 10 years. We need to foster an environment in which surgical innovation is encouraged through medical curriculum changes, multidisciplinary collaboration opportunities, and dedicated faculty resources.